2020
DOI: 10.1038/s41598-020-71532-7
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the cardiovascular autonomic control in healthy subjects during a passive head-up tilt test

Abstract: A mathematical model is proposed for the autonomic control of cardiovascular system, which takes into account two separated self-exciting sympathetic control loops of heart rate and peripheral vascular tone. The control loops are represented by self-exciting time-delay systems and their tone depends on activity of the aortic, carotid, and lower-body baroreceptors. The model is used to study the dynamics of the adaptive processes that manifest in a healthy cardiovascular system during the passive head-up tilt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
3
26
0
Order By: Relevance
“…According to the results from [23], infection by different types of viruses can increase the concentration of ACE2. Additionally, similar effects can be caused by some pathologies affecting RAS (diabetes, kidney disease) [23], some pathologies of the cardiological [5] and gynecological profile [24][25], as well as changes in the physical condition [16], as was shown in our previous studies. The group-averaged values of the S index were significantly different between the groups of healthy volunteers and COVID-19 patients.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…According to the results from [23], infection by different types of viruses can increase the concentration of ACE2. Additionally, similar effects can be caused by some pathologies affecting RAS (diabetes, kidney disease) [23], some pathologies of the cardiological [5] and gynecological profile [24][25], as well as changes in the physical condition [16], as was shown in our previous studies. The group-averaged values of the S index were significantly different between the groups of healthy volunteers and COVID-19 patients.…”
Section: Discussionsupporting
confidence: 73%
“…The phase analysis of CVS was shown to be a promising tool for clinical practice, in particular, for correcting the therapy in patients with hypertension and after myocardial infarction [13][14][15]. We showed that the total percentage of phase synchronization index (S index) was a sensitive index of CVS status [16,17] and was an index for specific pathologies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Transient response validation . The model is able to accurately reproduce transient responses following change of posture for the most common hemodynamic parameters—e.g.„ MAP, HR, CO, SV , and TPR refer to Critchley et al ( 1997 ); Toska and Walløe ( 2002 ); Youde et al ( 2003 ); Heldt ( 2004 ); Olufsen et al ( 2005 ); van Heusden et al ( 2006 ); Truijen et al ( 2012 ); Sundblad et al ( 2014 ); Williams et al ( 2014 ); Lau and Figueroa ( 2015 ), and Ishbulatov et al ( 2020 )—both reported in the literature and recorded in our in vivo measurements. Figure 4 shows beat-to-beat hemodynamic parameters adjustment to HUT, reaching upright posture (70°) within 17.5 s (4°/s).…”
Section: Resultsmentioning
confidence: 99%
“…According to a number of studies, the baroreflex and the processes of autonomic control determine the complex dynamics of blood circulation, in particular, the non-linear dynamics of heart rhythm ( Tan, 2013 ; Ernst, 2017 ; Karavaev et al, 2019 ). It is known that autonomic control loops are sensitive to changes in the physiological state of healthy subjects ( Ivanov et al, 1999 ; Valente et al, 2018 ; Ishbulatov et al, 2020 ). There is a significant change in baroreflex functions with aging ( Sharma and Goodwin, 2006 ; Schumann et al, 2010 ; Shiogai et al, 2010 ; Elliott et al, 2016 ; Parashar et al, 2016 ; Natarajan et al, 2020 ; Pietri and Stefanadis, 2021 ).…”
Section: Introductionmentioning
confidence: 99%